Assessment of Rhodopirellula rubra as a supplementary and nutritional food source to the microcrustacean Daphnia magna - Marinho, Maria da Conceição (2022)
The daily use of the planctomycete Rhodopirellula rubra as an alternative or supplementary food source for Daphnia magna and its feasibility in the nutrition of transgenerational populations were studied. The life history parameters, fatty acids (saturated, mono- and polyunsaturated; SFAs, MUFAs and PUFAs), glycogen and protein contents of organisms during feeding assays and of the first generation were analysed. An increase in the yields of D. magna with the increase of the cell concentration of R. rubra was evident, but overall, bacteria supplied as the only food source was nutritionally insufficient as observed for all the parameters analysed. However, when R. rubra was added as supplement to the microalgae Raphidocelis subcapitata a significant improvement in the life history parameters was observed namely in the reproductive output and the somatic growth rate. The identified SFAs, MUFAs and PUFAs were the fatty acids more abundant in daphniids, and the feed regimens influenced daphniids fatty acid profiles. Additionally, the mixed diet resulted in a larger number and size of offspring in the different F1 broods as also observed with the results of F0 generation. The pink colouration present in D. magna body and eggs confirmed that bacteria were absorbed, the pigment(s) retained and passed on to the next generation. Our results showed that R. rubra can play an essential role in D. magna diet as a nutritional supplement showing potential biotechnological applications.